2021
DOI: 10.1016/j.euo.2021.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variants Identified in Patients with Early-onset Renal Cell Carcinoma Referred for Germline Genetic Testing

Abstract: Background: Despite guidelines recommending genetic counseling for patients with early-onset renal cell carcinoma (RCC), studies interrogating the spectrum of germline mutations and clinical associations in patients with early-onset RCC are lacking. Objective: To define the germline genetic spectrum and clinical associations for patients with early-onset RCC diagnosed at age 46 yr who underwent genetic testing. Design, setting, and participants: We retrospectively identified patients with early-onset RCC who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…17 In the Copenhagen General Population Study, 18 the c.1100del variant was associated with breast and stomach cancers and enriched in kidney cancers and sarcomas, but this was not significant after correcting for multiple comparisons. CHEK2 PVs have been associated with colorectal, kidney, prostate, and thyroid cancers, 11,[19][20][21][22][23][24] but these findings are limited by small sample sizes and high genetic homogeneity.…”
mentioning
confidence: 99%
“…17 In the Copenhagen General Population Study, 18 the c.1100del variant was associated with breast and stomach cancers and enriched in kidney cancers and sarcomas, but this was not significant after correcting for multiple comparisons. CHEK2 PVs have been associated with colorectal, kidney, prostate, and thyroid cancers, 11,[19][20][21][22][23][24] but these findings are limited by small sample sizes and high genetic homogeneity.…”
mentioning
confidence: 99%
“…Furthermore, patients with VHL disease with CHEK2 germline mutation seem to have more severe symptoms, especially for RCC. Some studies have also demonstrated that CHEK2 germline mutations could be detected in early-onset RCC or associated with renal cancer 30 36. Coincidentally, a recent case report showed that an earlier age of onset of pancreatic neuroendocrine tumour was observed in a patient with both VHL and SDHA germline mutations 37.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of NGS technology has made the identification of VHL mutations easier 30. Simultaneously, it has facilitated the sequencing of numerous genomes and identification of de novo mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The Nordic Twin study has placed the genetic heritability of RCC as high as 38% 2 , however, only a fraction of the heritability is explained by currently identified rare and common RCC risk loci. Moving beyond known RCC risk genes (eTable 1) 3,4 , several pan-RCC studies have reported rare germline PVs in DNA damage repair (DDR) genes such as CHEK2, ATM, or BRCA1/2 [5][6][7][8][9][10] , suggesting that inherited defects in DDR may contribute to RCC risk. However, most studies lacked ancestry-matched cancer-free controls to formally test these hypotheses.…”
Section: Introductionmentioning
confidence: 99%